The Role of Personnel and Human Resource Development Agency in Improving Discipline of State Civil Servants in Ciamis Regency - zahra, Shifa; Arya Nurrahim; Citra Laila Hafiedzah; Tio Alpaisal; Asep Nurwanda (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract To achieve a government bureaucracy with integrity in accordance with the principles of good governance, it is essential to have regulations that can enforce the performance discipline of Civil Servants. The discipline of Civil Servants plays a crucial role in ensuring order, the smooth execution of tasks, productivity, and providing legal certainty in carrying out duties based on a career and performance system. Discipline is an effort made to direct employees' behavior to align with the organization's goals. In Ciamis Regency, the Human Resources and Development Agency has a significant role in fostering, supervising, and enforcing the discipline of Civil Servants through training programs, socialization, and handling violations based on Government Regulation Number 94 of 2021 regarding Civil Servant Discipline. This research aims to explore the role of the Human Resources Development Agency of Ciamis Regency in enhancing the discipline of State Civil Apparatus. The method used in this study is a descriptive qualitative approach with data collection through observation and interviews. The results of the observations indicate several disciplinary violations committed by the State Civil Apparatus, which were followed up with firm actions by the Human Resources Development Agency. These findings indicate that the Human Resources Development Agency has a strategic role in maintaining bureaucratic integrity through the implementation of objective and consistent discipline. Thus, the enhancement of institutional capacity and the understanding of State Civil Apparatus must continue to be deepened to support the creation of good governance.  Keywords: Role, Work Discipline, State Civil Apparatus